Functional and Molecular Characterization of the Halomicrobium sp. IBSBa Inulosucrase - TOKSOY ÖNER, EBRU (MDPI, 2021)
Fructans are fructose-based (poly)saccharides with inulin and levan being the best-known ones. Thanks to their health-related benefits, inulin-type fructans have been under the focus of scientific and industrial communities, though mostly represented by plant-based inulins, and rarely by microbial ones. Recently, it was discovered that some extremely halophilic Archaea are also able to synthesize fructans. Here, we describe the first in-depth functional and molecular characterization of an Archaeal inulosucrase from Halomicrobium sp. IBSBa (HmcIsc). The HmcIsc enzyme was recombinantly expressed and purified in Escherichia coli and shown to synthesize inulin as proven by nuclear magnetic resonance (NMR) analysis. In accordance with the halophilic lifestyle of its native host, the enzyme showed maximum activity at very high NaCl concentrations (3.5 M), with specific adaptations for that purpose. Phylogenetic analyses suggested that Archaeal inulosucrases have been acquired from halophilic bacilli through horizontal gene transfer, with a HX(H/F)T motif evolving further into a HXHT motif, together with a unique D residue creating the onset of a specific alternative acceptor binding groove. This work uncovers a novel area in fructan research, highlighting unexplored aspects of life in hypersaline habitats, and raising questions about the general physiological relevance of inulosucrases and their products in nature.
Keywords: fructan; inulin; inulosucrase; Haloarchaea; LEUCONOSTOC-CITREUM; SUBSTRATE-SPECIFICITY; PRODUCT SPECIFICITY; CRYSTAL-STRUCTURE; BIOFILM FORMATION; I-TASSER; LEVANSUCRASE; LEVAN; TEMPERATURE; FRUCTANS